A retrospective cohort of invasive fusariosis in the era of antimould prophylaxis. (24th June 2019) - Fernández-Cruz, Ana; Semiglia, María Auxiliadora; Guinea, Jesús; Martínez-Jiménez, María del Carmen; Escribano, Pilar; Kwon, Mi; Rodríguez-Macías, Gabriela; Chamorro-de-Vega, Esther; Rodríguez-González, Carmen; Navarro, Raquel; Galar, Alicia; Sánchez-Carrillo, Carlos; et al.
Abstract: Mould-active prophylaxis is affecting the epidemiology of invasive mycoses in the form of a shift toward less common entities such as fusariosis. We analyze the characteristics of invasive fusariosis and its association to antifungal prophylaxis in a retrospective cohort (2004–2017) from a tertiary hospital in Madrid, Spain. Epidemiological, clinical, microbiological, and antifungal consumption data were retrieved. Isolates were identified to molecular level, and antifungal susceptibility was tested. Eight cases of invasive fusariosis were diagnosed. Three periods were identified according to incidence: <2008 (three cases), 2008–2013 (zero cases), >2014 (five cases). All except one case involved breakthrough fusariosis. During the earliest period, the episodes occurred while the patient was taking itraconazole (two) or fluconazole (one); more recently, while on micafungin (three) or posaconazole (one). Early cases involved acute leukemia at induction/consolidation, recent cases relapsed/refractory disease ( P = .029). Main risk factor for fusariosis (62.5%) was prolonged neutropenia (median 44 days). Galactomannan and beta-D-glucan were positive in 37.5% and 100% of cases, respectively. All isolates except F. proliferatum presented high minimal inhibitory concentrations (MICs) against the azoles and lower MIC to amphotericin B. Most patients received combined therapy. Mortality at 42 days was 62.5%. Resolution of neutropenia was associated with survival ( P = .048). Invasive fusariosis occurs as breakthrough infection in patients with hematologic malignancy, prolonged neutropenia, and positive fungal biomarkers. Recent cases were diagnosed in a period of predominant micafungin use in patients who had more advanced disease and protracted neutropenia and for whom mortality was extremely high. Resolution of neutropenia was a favorable prognostic factor.